Timing of Change in Criminal Offending Around Entrance into Parenthood: Gender and Cross-Country Comparisons for At-Risk Individuals - Zoutewelle-Terovan, Mioara (Journal of quantitative criminology, 2016)
Objectives This article examines the timing of change in criminal offending relative to entrance into parenthood, in light of four competing theoretical frameworks (social control, routine activities, strain and cognitive transformation). Moreover, it analyzes whether criminal developments over time are gender- or country-specific. Methods Using samples of men and women at risk of offending in the Netherlands and Norway, this study investigates monthly changes in offending probabilities around the time of first birth (5 years before, 5 years after). The implemented smoothing splines technique allowed for a flexible exploration of changes in offending probabilities for both pre-childbirth and post-childbirth periods. Results The results show that the probabilities to offend decline ahead of childbirth for all individuals analyzed. The post-childbirth period is characterized by increases in offending probabilities. However, in these overall trends, the exact timing and magnitude of change differs by gender and country of residence. Conclusions The results offer partial support for the cognitive transformation hypothesis because offending rates decline before childbirth. The post-childbirth period converges with assumptions of the strain theory (for males in particular) because offending probabilities increase in this period. Additional analysis investigating changes in property offending shows that economic strain does not explain the upward trend of the overall offending after childbirth.